The Czech Republic: From the Center of Christendom to the Most Atheist Nation of the 21st Century, Part 1, The Persecuted Church: The Clandestine Catholic Church (Ecclesia Silentii) in Czechoslovakia During Communism 1948-1991 - Vitkovic, Scott (Occasional papers on religion in Eastern Europe, 2023)
This research examines the most important historical, political, economic, social, cultural, and religious factors before, during, and after the reign of Communism in Czechoslovakia from 1918 to 2021 and their effect on the extreme increase in atheism and decrease in Christianity, particularly Roman Catholicism, in the present-day Czech Republic. It devotes special attention to the role of the Clandestine Catholic Church (Ecclesia Silentii) and the changing policies of the Holy See vis-à-vis this Church, examining these policies' impact on the continuing decline of Roman Catholicism in the Czech Republic after the collapse of Communism. The article also deals with Pope Pius XII's Secret Mandates of 1948-1950, the Second Vatican Council, and the Holy See's Ostpolitik. Scholars, who previously relied only on the views of the Czechs, blame the unprecedented drop in Christianity, the near-total destruction of the Catholic Church, and the rise in atheism on the Czechoslovak communist government's four decades of totalitarianism. Although the increase in atheism and decrease in Christianity were substantial during the era of Communism from 1948 to 1989, our data indicate that the decline in Christianity, particularly the historically predominating Roman Catholicism, did not commence with the 1948 communist coup d'état but traces its origins to the breakdown of the Austro-Hungarian Empire after the conclusion of WWI and the establishment of Czechoslovakia on October 28, 1918. What's more, this research shows that the most significant and unprecedented steep deterioration of the Christian Faith, namely Roman Catholicism, did not occur during the era of Communism but only after the Czechoslovak communist government collapsed in 1989. This massive decay did not happen even during the most extraordinary communist persecution of the Catholic Church during the era of Stalinism in Czechoslovakia. This research further finds that the Holy See's ill-advised policies and systematic, sustained, and prevalent failures in leadership, guidance, and teachings are responsible for the near destruction of the Roman Catholic Church and especially the end destruction of the Clandestine Catholic Church (Ecclesia Silentii), in the Czech and Slovak Republics after the fall of Communism. These failures furthermore contributed to the Czech Republic, the historical lands of Bohemia and Moravia that once were in the center of Christendom, degenerating into the most atheist country in Europe and the world today.